Continuous Biohydrogen Production by a Degenerated Strain of Clostridium Acetobutylicum Atcc 824 - Quintero-Suarez, J (Elsevier Ltd, 2021)
Degenerated strains of Clostridium acetobutylicum lack the ability to produce solvents and to sporulate, allowing the continuous production of hydrogen and organic acids. A degenerated strain of Clostridium acetobutylicum was obtained through successive batch cultures. Its kinetic characterization showed a similar specific growth rate than the wild type (0.25 h−1), a higher butyric acid production of 6.8 g·L−1 and no solvents production. A steady state was reached in a continuous culture at a dilution rate of 0.1 h−1, with a constant hydrogen production of 507 mL·h−1, corresponding to a volumetric rate of 6.10 L·L−1 d−1, and a yield of 2.39 mol of H2 per mole of glucose which represents 60% of the theoretical maximum yield. These results suggest that the degeneration is an interesting alternative for hydrogen production with this strain, obtaining a high hydrogen production in a continuous culture with cells in a permanent acidogenic state. © 2020 Hydrogen Energy Publications LLC